Estimation of daily diffuse solar radiation from clearness index, sunshine duration and meteorological parameters for different climatic conditions. (October 2021) - Tahir, Zia ul Rehman; Hafeez, Saiqa; Asim, Muhammad; Amjad, Muhammad; Farooq, Muhammad; Azhar, Muhammad; Amjad, Ghulam Murtza
Abstract: This study aims to evaluate performance of 30 models (15 selected from literature and 15 newly developed) to estimate diffuse horizontal irradiance ( Hd ) using high-quality measurements for nine stations having different climatic conditions. The models (divided into three categories) are based on extraterrestrial global horizontal irradiance ( Ho ) and measured global horizontal irradiance ( Hg ) using sunshine duration ratio, clearness-index, temperature, relative humidity, and periodicity factor as input parameters. The performance of models was evaluated using statistical parameters; the performance of H g based models (Category-II and Category-III) is better than Ho based models (Category-I). The performance of newly developed models in three categories is better than best models selected from the literature, due to higher number of input parameters and higher powers used. The best models in Category-I, Category-II and Category-III have rMBE (rRMSE) ranges from −0.3 to 0.6% (14 to 20%), −0.6 to 0.1% (10 to 17%) and −0.3 to 0.0% (10 to 17%) respectively. The performance of models varies in different zones, and different stations within same zone, due to variations of climatic conditions. The best models have rMBE within ±1% and rRMSE < 20%, and can be used for initial resource assessment of commercial solar PV projects for potential locations.